Portfolio Overlapping Bias in Tests of the Fama–French Three‐Factor Model. (13th August 2015) - Tauscher, Kathrin; Wallmeier, Martin
Abstract: In the standard approach of the three‐factor model of Fama and French (1993 ), both the test portfolios and the SMB and HML factor portfolios are formed on the basis of size and the book‐to‐market ratio. Thus, a potential overlapping bias in time‐series regressions arises. Based on a resampling method and a split‐sample approach, we provide an in‐depth analysis of the effect of overlapping for a broad sample of European stocks. We find that the overlapping bias is non‐negligible, contrary to what seems to be the general opinion.